Cholangiocarcinoma Presenting as Linitis Plastica with Unusual Metastases to the Psoas Muscle and Urinary Bladder. Issue 1 (2018) - Banerjee, Debdeep; Raghavapuram, Saikiran; George, Nayana E.; Korourian, Soheila; Fedda, Faysal A.; Perisetti, Abhilash; Tharian, Benjamin
ABSTRACT : N/A: Cholangiocarcinoma offers poor prognosis. Infrequent sites of metastasis are poorly described and often diagnostically delayed or missed. Bile duct brush cytologies provide poor diagnostic sensitivity/specificity. We present an unusual case of cholangiocarcinoma in a 34‐year‐old woman with rare distant metastasis to the psoas muscle and urinary bladder. It is the first case of metastatic cholangiocarcinoma presenting as linitis plastica, and our patient is the youngest to be described with metastatic cholangiocarcinoma to the psoas muscle leading to diagnosis. We conclude that seemingly idiopathic biliary strictures that fail to respond to testing should prompt alarm and referral for cholangioscopy, where available.